Shonen note : boy soprano. 8 - Kamatani, Yuhki (Kodansha USA Publishing, LLC, 2024)
When the town of Kawami has to accept dismal results from the vote on the industrial waste disposal facility, the City Opera troup hopes to lift spirits with music. Yutaka has been on a long journey of self-discovery, coming to terms with every aspect of his personality, but Midori's harsh words about his singing could send him into a self-defeating spiral.